Penahanan Anak yang Melakukan Tindak Pidana Pencurian dengan Kekerasan (Studi Kasus Nomor: 6/Pid.Sus-Anak/2017/PN Dps) - GD. Bagus Maesha Kumara; Anak Agung Sagung Laksmi Dewi; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2019)
Abstract Children are the next generation of the nation. Therefore, every child should get his right to play, learn and socialize. But the situation will turn around if the child commits a crime, such as a case of sexual harassment, violence against minors, cases of theft with violence. Law Number 11 of 2012 concerning Child Criminal Justice System. This SPPA Law is a substitute for Law Number 3 of 1997 concerning Juvenile Courts. The Juvenile Court Law is considered to be no longer in accordance with legal needs in the community and has not comprehensively provided special protection to children who are faced with the law. From this background, the problem will be discussed, (1) is Detention of children in a case decisions number: 6 / Pid.Sus-Anak / 2017 / PN Dps, has fulfilled the Child Criminal Justice System? And (2) what are the judges' considerations in criminal imposing acts on whom children commit acts of theft by violence? This study uses normative legal research methods, uses a statutory approach and a conceptual approach, and examines the primary legal material and secondary legal material. The results of this study indicate that (1) Knowing the legal provisions for the detention of children, according to the juvenile justice system in case decisions number: 6 / Pid.Sus-Anak / 2017 / PN Dps. (2) Knowing the judge's consideration in criminal imposing acts on whom the children criminal commit acts of theft by violence. Keywords: Children; judge considerations; theft by violence Abstrak Anak ialah penerus bangsa dimasa depan. Karena anak wajib diberikan hak untuk belajar serta bermain. Tetapi apabila anak melakukan tindak pidana keadaan akan berbalik. UU Tentang SPPA. UU SPPA ini adalah pengganti dari UU tentang Pengadilan Anak. UU Pengadilan Anak dinilai sudah tidak sesuai lagiuntuk melindungi hak-hak anak dihadapan hukum. Dari latar belakang tersebut maka permasalahannya: (1) Apakah Penahanan terhadap anak dalam putusan perkara nomor: 6/Pid.Sus-Anak/2017/PN Dps, sudah memenuhi Sistem Peradilan Pidana Anak? dan (2) Bagaimanakah pertimbangan hakim didalam menjatuhkan pidana kepada Anak yang melakukan tindak pidana pencurian dengan kekerasan ? Penulisan ini menggunakan metode penelitian hukum normatif, menggunakan pendekatan perundang-undangan dan pendekatan koseptual, mengkaji dari bahan hukum primer dan bahan hukum sekunder. Hasil penelitian ini menunjukan bahwa (1) Mengetahui ketentuan hukum penahanan anak menurut SPPA dalam putusan perkara nomor: 6/Pid.Sus-Anak/2017/PN Dps. (2) Mengetahui pertimbangan hakim didalam menjatuhkan pidana kepada anak yang melakukan tindak pidana pencurian dengan kekerasan. Kata Kunci: Anak; pertimbangan hakim; pencurian dengan kekerasan